Facile and template-free synthesis of nano-macroporous LaCoO3 perovskite oxide for efficient diesel soot oxidation - Neha; Singh, Satya Vir (Springer Science and Business Media B.V., 2022)
The basic LaCoO3 perovskite oxides were prepared by the series of methods (reverse co-precipitation, citric acid aided sol–gel, glycine assisted solution combustion), underwent physicochemical characterization (XRD, FTIR, BET, XPS and SEM), followed by their soot oxidation activity tests in both “loose” and “tight” conditions of soot-catalyst contact. The activity tests revealed that the LaCoO3 catalyst formed using glycine assisted combustion synthesis gives the best performance with the T10, T50, and T90 at 361 °C, 404 °C and 445 °C, respectively, in loose contact conditions and T10, T50, and T90 at 306 °C, 330 °C and 355 °C, respectively, in tight contact conditions. Its outstanding performance can be attributed to its unique morphology consisting of scaffolds having an extensively interconnected macroporous network with macropores having nanoporous struts as walls as evidenced by SEM results. Such morphology makes the active sites of inner pores accessible to the gaseous (air) as well solid reactant (soot particles), thereby benefitting soot oxidation reaction.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Nano-macroporous; Glycine; LaCoO3; Scaffold; Soot oxidation